Distribution and quantification of antibiotic resistance genes in a large subalpine lake (Lugano Lake) and tributary rivers - Federica Mauri; Elisa Pianta (Journal of Global Antimicrobial Resistance, 2023)
ABSTRACT: Objectives: Antibiotic resistance genes (ARGs) are causing increasing problems, especially in clinical settings. Nowadays, they are considered important environmental contaminants, but little is known about their fate in the environment or how they affect natural microbial populations. In the environment, especially in water affected by anthropic activities such as discharge of hospital, urban, and industrial wastewater treatment plant (WWTP) and agricultural runoff, antibiotic determinants may become part of the environmental gene pool, spread horizontally, and be ingested by humans and animals via contaminated food and drinking water.The aim of this work was to monitor long-term the presence of antibiotic resistance determinants in water samples collected from a subalpine lake and some tributary rivers located in the southern part of Switzerland, and to assess if anthropic activities could influence the distribution of antibiotic resistance genes present in water environments. Methods: We analysed water samples by qPCR to quantify five antibiotic resistance genes that confer resistance to the major classes of antibiotics used in clinical and veterinary settings (β-lactams, macrolides, tetracycline, quinolones, and sulphonamides). Water samples were collected from January 2016 to December 2021, from three rivers located in south Switzerland and from five different sites of Lugano Lake. Results: The most abundant genes were sulII, followed by ermB, qnrS, and tetA; they were found especially in the river influenced by wastewater treatment plants and in the lake near the potable water uptake plant. We observed an overall decrease in the number of resistance genes during the three years. Conclusions: Our results indicate that the aquatic ecosystems monitored in this study are a reservoir of ARGs and could potentially be a setting for the transmission of resistance from the environment to humans.